Granulomatous slack skin T-cell lymphoma: an important differential diagnosis with giant cell tumor of soft tissue - André Ricardo Adriano; Tiago Silveira Lima; Maxime Battistella; Martine Bagot (Sociedade Brasileira de Dermatologia, 2015)
Abstract: Granulomatous slack skin is an indolent T-cell lymphoma, considered to be a variant of mycosis fungoides. Clinically it is characterized by areas of redundant skin, wrinkled, inelastic, with variable erythema and infiltration besides a poikilodermic surface. A differential diagnosis unknown to most dermatologists is the giant cell tumor of soft tissue, which is an extremely rare low-grade sarcoma. The authors report a patient who had undergone extensive surgery because of a primary diagnosis of giant cell tumor of soft tissue, but which proved to be granulomatous slack skin after a second interventional procedure with confirmatory histopathology.